Strengthening Families: Social Connections - Larry F. Forthun; Samantha Carannante; David C. Diehl (EDIS)
Whether it is family members, neighbors, friends, or coworkers, it is vital that parents have people in their lives that can provide social support. This 3-page fact sheet suggests several ways to create new social connections and improve existing ones. Written by Larry F. Forthun, Samantha Carannante, and David C. Diehl, and published by the UF Department of Family, Youth and Community Sciences, December 2011.